Pengaruh Budaya Organisasi dan Stres Kerja terhadap Kepuasan Kerja Karyawan pada PT. Kereta Api Indonesia Persero Daop 8 Surabaya - Sista Prilia Nisa Amilia; Dwiarko Nugrohoseno (BISMA (Bisnis dan Manajemen), 2018)
Changes require organizational changes to its organizational culture as the culture as a reference to coordinate the behavior of employees to achieve organizational goals, and of the employees who adaptation back to a new environment. This study aims to describe and analyze wheter organizational culture and job stress employee job satisfaction. The study took place at PT. Kereta Api Indonesia Persero Daop 8 Surabaya. Sampling technique that used was proportionate stratified random sampling. Methods of the statistical analysis that used were multiple linear regression with the help of SPSS 1.8 software. the results showed that organizational culture have a significant positive influence on employee job satisfaction, job stress had not significant influence on employee job satisfaction, organizational culture and job stress have a significant simultant influence on employee job satisfaction.